BIBLIOMETRIC ANALYSIS OF PRIMARY SCHOOL READINESS IN ORGANIZING INCLUSIVE EDUCATION USING VOSVIEWER - Nikmatusshobrina, Rani Azizah; Haerani, Rosita Putri Rahmi; Aras, Tiara Oktaviani; Cahyani, Almaidah Rifma; Anggraini, Dian (Jurusan Pendidikan Luar Biasa, 2025)
This research makes an important contribution to education policy makers and practitioners to improve the readiness and effectiveness of inclusive education at the primary level. This study aims to map the trends and directions of research on the readiness of primary schools to deliver inclusive education in Indonesia. A bibliometric approach was used with the help of VOSviewer software on 50 articles from the Scopus and Sinta databases published between 2020-2025. The analysis showed four main clusters: school readiness, inclusive education, infrastructure readiness and implementation. The keywords “inclusive education” and “implementation” were the most dominant, with an increasing trend of publications, especially from international journals. However, research gaps remain, such as the lack of longitudinal studies, the lack of integration of qualitative-quantitative approaches and the limited exploration of technology in inclusive education. These findings provide important insights for policy makers, researchers and education practitioners in developing data-driven strategies to improve primary schools' readiness to deliver inclusive education effectively and sustainably.